2017
DOI: 10.1016/j.snb.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in optical fiber hydrogen sensors

Abstract: A review for optical fiber hydrogen sensors based on palladium (Pd) and tungsten oxide (WO 3) thin films is presented, with specific focus on the measurement methods, probe structures, and sensing properties of different sensors. Firstly, the theoretical models behind the optical fiber hydrogen sensors, as well as their practical limitations, are addressed. Secondly, four mainstream measurement methods, including intensity, fiber Bragg grating (FBG), interferometer, surface plasmon resonance (SPR), which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 87 publications
1
80
0
3
Order By: Relevance
“…9(c) shows the correlation between variation in sensitivity of the AZO sensor and ethanol concentrations ranging from 5 to 500 ppm at 332°C. At lower concentration, it can be observed that for all the tested gases, there is a linear relationship between log (S -1) and log (C), which is in good agreement with the theory of power laws for semiconductor sensors [21,22] …”
Section: Response-recovery Characteristicsupporting
confidence: 77%
See 1 more Smart Citation
“…9(c) shows the correlation between variation in sensitivity of the AZO sensor and ethanol concentrations ranging from 5 to 500 ppm at 332°C. At lower concentration, it can be observed that for all the tested gases, there is a linear relationship between log (S -1) and log (C), which is in good agreement with the theory of power laws for semiconductor sensors [21,22] …”
Section: Response-recovery Characteristicsupporting
confidence: 77%
“…The response-recovery behavior is an important characteristic for evaluating the property of gas sensors [21]. Fig.…”
Section: Response-recovery Characteristicmentioning
confidence: 99%
“…More recently, various optical sensor principles have been proposed for H 2 monitoring [44][45][46][47][48][49][50][51][52][53][54][55][56]. Sensors based on the H 2 uptake in palladium appear particularly promising.…”
Section: Emerging Spr Sensor Technologies For Admentioning
confidence: 99%
“…The volume expansion of palladium films or nanoparticles caused by metal-hydride formation can be measured very accurately using optical techniques [44,45,49,52,54,55]. Additionally, the SPR of gold (when coupled to palladium in a layer stack), can be measured accurately, with the plasmon resonance frequency being modulated by the hydrogenation of the palladium layer [48,50,53].…”
Section: Emerging Spr Sensor Technologies For Admentioning
confidence: 99%
“…In these cases, the typical probe structures were associated to the intrinsic physicochemical characteristics of the sensing thin film that change according to the H 2 concentration, so the transmitted probe optical signal will also carry the corresponding signature through intensity evolutions [3][4][5][6][7][8][9][10] or wavelength shifts [11][12][13][14][15][16][17][18][19][20]. In addition, many other studies targeted the optical response modifications based on interferometers [21][22][23][24][25][26] or surface plasmon resonance [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%